Neurological Applications of PET/MR - Miller-Thomas, Michelle M. (Magn Reson Imaging Clin N Am, 2017)
PET/MR benefits neurological clinical care and research by providing spatially and temporally matched anatomic MR imaging, advanced MR physiologic imaging, and metabolic PET imaging. MR imaging sequences and PET tracers can be modified to target physiology specific to a neurological disease process, with applications in neuro-oncology, epilepsy, dementia, cerebrovascular disease, and psychiatric and neurological research. Simultaneous PET/MR provides efficient acquisition of multiple temporally matched datasets, and opportunities for motion correction and improved anatomic assignment of PET data. Current challenges include optimizing MR based attenuation correction and necessity for dual expertise in PET and MR.